Paradigm pioneers - Barker, Joel Arthur (Burnsville : Charthouse International Learning, 1991)
Barker explores the nature of paradigm pioneer. The advocates becoming an anticipator of changes and innovation in order to help an organisation develop new products and services
Keywords: Business forecasting; Forecasting; Paradigms (Social sciences).; Success in business